Flexible 3D Architectured Piezo/Thermoelectric Bimodal Tactile Sensor Array for E‐Skin Application. Issue 39 (30th August 2020) - Zhu, Pengcheng; Wang, Yalong; Wang, Yao; Mao, Hongye; Zhang, Qiang; Deng, Yuan
Abstract: Electronic skin (e‐skin) functions as human–machines interaction interfaces, holding great promise in future personal health monitoring and endowing robots with capability of sense of touch. Despite recent exciting progress in e‐skin research, accurate discrimination of various tactile inputs remains a great challenge yet. A 3D processing technique is demonstrated here combining laser fabrication and screen printing to construct vertically architectured pressure/temperature bimodal active sensor employing all organic functional materials, i.e., piezoelectric poly(vinylidene fluoride‐ co ‐trifluoroethylene) and thermoelectric polyaniline‐based composites. The sensor transforms pressure and temperature stimuli into two independent electrical signals without interference, exhibiting high temperature sensing sensitivity (109.4 µV K −1 ) with rapid response time (0.37 s) and superior pressure sensing sensitivity over a wide range (100 Pa to 20 kPa). Finite element analyses further explain the thermal harvesting performance of the sensor. Applications of sensor as e‐skin in various temperature/stress perception scenarios and its stability are demonstrated. Further, a 4 × 4 pixel bimodal tactile sensor array is integrated for the first time, presenting accurate spatial distribution mapping of pressure/temperature signals simultaneously without interference, and functions without external power supply due to its intrinsic working principle. This study thus moves a step toward multifunctional flexible electronics for e‐skin applications. Abstract : Despite recent exciting progress in electronic skin research, accurate discrimination of various tactile inputs remains a great challenge. A vertically architectured 4 × 4 pressure/temperature bimodal tactile sensor array is integrated for the first time via a 3D processing technique employing all‐organic piezoelectric and thermoelectric materials, presenting accurate mapping of pressure/temperature signals independently.